2012
DOI: 10.1007/s13224-012-0179-z
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Skin

Abstract: Careful history taking and examination will help us to identify each condition clinically and appropriate management can be instituted for the well-being of the mother and the fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
3
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 35 publications
2
31
3
12
Order By: Relevance
“…Nail changes are also mentioned among the physiological skin changes that occur during pregnancy. Until now, the reported changes encountered during pregnancy were leukonychia, transverse grooves, subungual hyperkeratosis, distal onycholysis, brittleness, and fragility in the nails . In our study, we did not detect any statistically significant difference between the pregnancy group and the control group regarding trachyonychia, leukonychia, subungual hyperkeratosis, onycholysis, chromonychia, pitting, splinter hemorrhage, and other nail findings.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Nail changes are also mentioned among the physiological skin changes that occur during pregnancy. Until now, the reported changes encountered during pregnancy were leukonychia, transverse grooves, subungual hyperkeratosis, distal onycholysis, brittleness, and fragility in the nails . In our study, we did not detect any statistically significant difference between the pregnancy group and the control group regarding trachyonychia, leukonychia, subungual hyperkeratosis, onycholysis, chromonychia, pitting, splinter hemorrhage, and other nail findings.…”
Section: Discussioncontrasting
confidence: 71%
“…Studies conducted almost 60 years ago reported that pregnancy increased the growth rate of nails . Several studies conducted since then have also reported that pregnancy accelerates nail growth, with references to these earlier studies . In addition, it has also been reported that leukonychia, subungual hyperkeratosis, distal onycholysis, transverse grooves, softening, and brittleness in nails might be encountered during pregnancy …”
Section: Introductionmentioning
confidence: 93%
“…All of these conditions can be linked to either profound hormonal, vascular, metabolic, or immune changes occurring during pregnancy and treatment can be difficult [59]. Unfortunately, treating psoriasis in pregnant and lactating women presents a special challenge.…”
Section: Pregnancymentioning
confidence: 99%
“…Gebelik karmaşık homonal, immünolojik, metabolik süreçlerin etkisiyle çok sayıda değişikliğin gözlendiği bir dönemdir [2][3][4] . Bu değişiklikler temelde gebeliğin fizyolojik değişiklikleri, GÖD ve GÖOH olarak sınıflan-dırılabilir.…”
Section: Discussionunclassified
“…Stria gravidarum, kloasma, tırnak değişiklikleri, diş eti değişiklikleri dermatoloji polikliniğine müracat eden gebelerde sık saptanan bulgular olarak bildirilmiştir 3,8,9 . Fizyolojik değişik-lik nedeniyle konsülte edilen gebe sayısının azlığı ve bunların primigravid oluşu, bu yakınmaların gebeleri direk olarak dermatolojiye yönlendirdiği ve ya uzman kontrolüne gereksinim hissettirmediğini düşündürdü.…”
Section: Discussionunclassified